Root and arbuscular mycorrhizal mycelial interactions with soil microorganisms in lowland tropical forest. Issue 1 (20th March 2013) - Nottingham, Andrew T.; Turner, Benjamin L.; Winter, Klaus; Chamberlain, Paul M.; Stott, Andrew; Tanner, Edmund V.J.
Abstract Tropical forests have high rates of soil carbon cycling, but little information is available on how roots, arbuscular mycorrhizal fungi (AMF), and free‐living microorganisms interact and influence organic matter mineralization in these ecosystems. We used mesh ingrowth cores and isotopic tracers in phospholipid fatty acid biomarkers to investigate the effects of roots and AMF mycelia on (1) microbial community composition, microbial carbon utilization, and hydrolytic enzyme activities for large, potted tropical trees and (2) enzyme activities and litter mass loss in a lowland tropical forest. Under the tropical tree, plant‐derived carbon was incorporated predominantly into bacterial groups in both rhizosphere and AMF‐only soils. Gram‐positive bacteria incorporated additional soil‐derived carbon in rhizosphere soils, which also contained the highest microbial biomass. For hydrolytic enzymes, β‐glucosidase and N‐acetyl β‐glucosaminidase activities were highest in rhizosphere soils, while phosphomonoesterase activity was highest in AMF‐only soil. In the forest, leaf litter mass loss was increased by the presence of roots, but not by the presence of AMF mycelia only. Root–microbial interactions influenced organic matter cycling, with evidence for rhizosphere priming and accelerated leaf litter decomposition in the presence of roots. Although AMF mycelia alone did not stimulate organic matter mineralization, they were a conduit of carbon to other soil microorganisms.